Mantenedor de espacio con extensión subgingival: Reporte de un caso - Soldevilla Galarza, Luciano Carlos (2003)
The space maintainer with subgingival extension like a distal wedge is an alternative treatment to prevent dental space loss or to preserve it where it has been lost temporaly second molar before permanent first molar eruption. This is a fixed mantained that fulfills its function with great success because of its permanent position, improving this way poor child collaboration. Here we show a clinical case with acceptable results